Merger mania! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The past few months have seen a spate of major companies getting together across the globe. It really is wild out there in 'merger mania' land, with big organisations gobbling up small ones and giants climbing clumsily into the same bed. There are...